2021
DOI: 10.3390/en15010090
|View full text |Cite
|
Sign up to set email alerts
|

Deliberation Platform for Energy Transition Policies: How to Make Complex Things Simple

Abstract: The energy transition from inefficient fossil-based to sustainable energy systems can face various lock-ins. There are no pathways that are free of stress. However, many routes are possible. A good understanding of the dynamic behavior of systems is crucial, and proper support tools are needed to assess the outcomes of every selected pathway. This study aims to develop an Internet-based interface tool for the national energy simulation model as a tool for a “hybrid forum”; study energy transition lock-ins in o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 51 publications
0
9
0
Order By: Relevance
“…Most models were simulated up to 2050, given the year's relevance for climate action plans as a landmark for achieving a net-zero global economy [38]. Regarding model development, only Blumberga et al [65] and Strapasson et al [66] mentioned the performance of workshops to gather insights on systems structures and stakeholders' expectations. Concerning the employment of models to aid policy-making, only Blumberga et al [65] reported on the development of an open Internetbased policy-aiding tool.…”
Section: Descriptive Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Most models were simulated up to 2050, given the year's relevance for climate action plans as a landmark for achieving a net-zero global economy [38]. Regarding model development, only Blumberga et al [65] and Strapasson et al [66] mentioned the performance of workshops to gather insights on systems structures and stakeholders' expectations. Concerning the employment of models to aid policy-making, only Blumberga et al [65] reported on the development of an open Internetbased policy-aiding tool.…”
Section: Descriptive Resultsmentioning
confidence: 99%
“…Residential energy demand, in particular, was calculated through exogenous urbanisation rates and household income [58]. From a technological perspective, demand was also influenced by the share of energy efficient and inefficient consumers [65]. Energy efficiency interventions are presented in Figure 3 as a A review of social aspects integration in system dynamics energy systems models result of technological development and behaviour changes [65].…”
Section: Supply-demandmentioning
confidence: 99%
See 2 more Smart Citations
“…The necessary data has been collected from statistical sources, scientific literature, and publicly available reports. A more detailed description of the developed SD model can be found in the authors' previous research [23]- [27]. The developed SD model is a comprehensive tool for the energy sector in Latvia that interconnects modeling of the related systems into the consistent structure.…”
Section: Development Of Sd Modelmentioning
confidence: 99%